2018
DOI: 10.4049/jimmunol.1700407
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anti-TIGIT Antibodies Regulate Development of Autoimmunity and Antitumor Immunity

Abstract: Coinhibitory receptors, such as CTLA-4 and PD-1, play a critical role in maintaining immune homeostasis by dampening T cell responses. Recently, they have gained attention as therapeutic targets in chronic disease settings where their dysregulated expression contributes to suppressed immune responses. The novel coinhibitory receptor TIGIT (T cell Ig and ITIM domain) has been shown to play an important role in modulating immune responses in the context of autoimmunity and cancer. However, the molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 17 publications
(45 reference statements)
6
115
0
Order By: Relevance
“…Moreover, we found that early T cell activation was significantly reduced after agonistic TIGIT ligation in vivo, which correlated with the considerably reduced production of pro-inflammatory cytokines. This is in line with previous reports demonstrating the potential of TIGIT to attenuate T cell responses 9,15,31 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, we found that early T cell activation was significantly reduced after agonistic TIGIT ligation in vivo, which correlated with the considerably reduced production of pro-inflammatory cytokines. This is in line with previous reports demonstrating the potential of TIGIT to attenuate T cell responses 9,15,31 .…”
Section: Discussionsupporting
confidence: 93%
“…1B), while the PD-1 expression on regulatory T cells remained unchanged over the course of chronic infection. The in vivo anti-TIGIT antibody (clone 1B4) was already shown to be non-depleting after immunization with MOG peptide 31 and we confirmed these findings in chronic LCMV infection ( Supplementary Fig. 1C).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations